ANALISA PROSES REPAIR CACAT POROSITY PADA SURFACE HASIL PENGELASAN SAMBUNGAN PENGELASAN SUBMERGED ARC WELDING PADA PLAT LQ 8 - Firmansyah, Tengku Mahendra; Susilo, Trisno; Hilmy, Zakwan; Tyas Adi, Fajar (JURNAL JALASENA, 2024)
Welding using the Submerged Arc Welding (SAW) method is one of the popular welding techniques in the manufacturing and construction industries. Even though SAW has advantages in high productivity and welding quality, it still faces challenges related to porosity defects that can arise during the welding process. Porosity defects are one of the serious problems that can reduce the strength, ductility, and corrosion resistance of welded joints. In this study, analysis of porosity defects in SAW welding was carried out. First, a literature study was carried out to understand the factors that influence the formation of porosity during SAW welding. These factors include the nature of the base material, the setting of welding parameters, the composition of the shielding gas, and the condition of the base metal surface. The results of this study indicate that the formation of porosity defects in SAW welding is strongly influenced by the setting of welding parameters and conditions in the field. This study provides better insight into the nature and characteristics of porosity defects in SAW welding, and provides guidance for reducing or avoiding porosity defects through proper control of welding parameters and good surface preparation. By reducing the porosity defect rate in SAW welding, it is hoped that it will increase the reliability and quality of the resulting welded joints, thereby meeting higher industrial standards and structural safety.